2014
DOI: 10.1111/btp.12136
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness, Forest Structure, and Functional Diversity During Succession in the New Guinea Lowlands

Abstract: Much of the world's tropical forests have been affected by anthropogenic disturbance. These forests are important biodiversity reservoirs whose diversity, structure and function must be characterized across the successional sequence. We examined changes in structure and diversity along a successional gradient in the lowlands of New Guinea. To do this, we measured and identified all stems ≥5 cm diameter in 19 0.25 ha plots ranging in age from 3 to >50 yr since disturbance. We also measured plant functional trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 64 publications
5
79
3
Order By: Relevance
“…While small, the number of studies addressing similar questions has increased rapidly in recent years (e.g., Alvarez-Añorve et al 2012;Becknell and Powers 2014;Dent et al 2013;Lasky et al 2014;Lebrija-Trejos et al 2010;Lohbeck et al 2013;Whitfeld et al 2014). In general, results from the present and previous studies provide increasingly strong evidence for the validity of this hypothesis across different tropical regions.…”
Section: Successional Shifts In Functional Strategiessupporting
confidence: 56%
See 3 more Smart Citations
“…While small, the number of studies addressing similar questions has increased rapidly in recent years (e.g., Alvarez-Añorve et al 2012;Becknell and Powers 2014;Dent et al 2013;Lasky et al 2014;Lebrija-Trejos et al 2010;Lohbeck et al 2013;Whitfeld et al 2014). In general, results from the present and previous studies provide increasingly strong evidence for the validity of this hypothesis across different tropical regions.…”
Section: Successional Shifts In Functional Strategiessupporting
confidence: 56%
“…Successional gradients are characterized by clear shifts in resources and environmental conditions, i.e., from high to low light availability, air temperature and soil moisture, and species composition, i.e., from shade-intolerant to shade-tolerant species Dent et al 2013;Lebrija-Trejos et al 2010;Norden et al 2009Norden et al , 2011a, which lend support to the idea that adaptations to resource availability shape successional patterns of community composition (Rees et al 2001;Tilman 1985). To date, the mechanisms driving these patterns in tropical secondary forests have been tested explicitly in regions that vary markedly in terms of climate, soil, landuse history, and landscape configuration (e.g., Becknell and Powers 2014;Dent et al 2013;Lohbeck et al 2013;Whitfeld et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 82%
See 2 more Smart Citations
“…At that time, seedling establishment of benefited from the opening of canopy gap Pometia resulting from logging activities where irradiance could reach understory. Most of the early seedling establishment in tropical rainforests require the irradiance to grow (DuahGyamfi et al 2014;Goodale et al 2014;Whitfeld et al 2014). On the other hand, the absence of larger individuals of Pometia in logged forest indicated that the logged forests are still recovering from logging impact.…”
Section: Structure Of Pometia In Unlogged and Logged Forestmentioning
confidence: 99%